Pengaruh Game Online Terhadap Perilaku Remaja - Hilda Asihatul Afiyah; Isak Iskandar (PT. Intelek Cendikiawan Nusantara, 2025)
This research examines the influence of online gaming on adolescent behavior based on data analysis from 10 respondents. The results show significant impacts of online gaming on various aspects of adolescent life with an average negative behavior score of 31.1 out of a maximum of 60 (standard deviation 14.34). The most common behaviors observed include losing track of time, postponing academic tasks, sleep pattern disturbances, and emotional changes such as irritability and stress. The research instrument proved highly reliable with a Cronbach's Alpha value of 0.988 and strong correlations between indicators (r > 0.90, p < 0.01). These findings are supported by previous research identifying negative impacts of online gaming addiction on adolescents' health, psychological, academic, and social aspects. Online gaming addiction is also associated with antisocial behavior, decreased interaction with family and friends, and increased aggressive behavior, especially when games contain violent elements. Family environment factors, particularly lack of parental firmness, contribute to increasing the risk of addiction. This research concludes that online gaming has a significant influence on changes in adolescent behavior, necessitating supervision and education from families and the environment to minimize negative impacts.